Rancang Bangun Alat Pencampuran Baglog Jamur Tiram Menggunakan Metode Design For Manufacturing & Assembling (DFMA) - Nur Islahudin; Ishar Udin Khoir (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2024)
This research was motivated by a need for more optimization in mixing and pouring baglog planting media into the plastic at Omah Jamur Ungaran. This mixing process has several drawbacks, such as baglog experiencing clumping, so sifting is needed. The pouring of baglog planting media is still done manually, pouring the mixing results into the soil and then putting it in plastic. It is feared that the pouring of baglog results into the ground has contaminated the place of pouring the results baglog mixing. They fear that the pouring baglog will result in the environment. There is contamination at the location of running the results of baglog mixing. This study aims to determine whether sifting and mixing can combine into one process and the method using Design for Manufacturing and Assembly methods. This study resulted in the design, calculations, and Static Stress Frame tests using the simulation feature of AutodeskFusion360, with a maximum capacity of 40kg, using a 1hp motor, rotation speed has 140 RPM. From study has the results, it was concluded this machine could produce results in 55 minutes, producing 150 Baglog, eliminating the sieving process installing an iron net with a size of 5mm, process mixing and pouring planting media baglog using the results of the machine design has made. Application of design for manufacturing and assembly method at design tool has simplified components of the previous machine into 12 parts at the machine has made.